Pengukuran Keterlibatan Pelajar Menggunakan Learning Analytic dan Metode Kanban - Tresnawati, Dewi; Septiana, Yosep; Hidayatno, Fachrul Ramdaniar (Institut Teknologi Garut, 2025)
Currently, Learning Management Systems (LMS) are widely used in schools. However, the features of LMS that are commonly used today are not yet capable of increasing student engagement in learning, especially in online learning. Learning analytics helps teachers identify learning targets, understand results, behaviors, and learning processes so that teachers can determine the right learning strategies. The purpose of this study is to apply learning analytics, measure student engagement in online learning using a Learning Management System built with the Kanban method and NodeJS framework as the backend. The Learning Management System has proven to be capable of generating data and information related to learning activities such as attendance, assessments, assignments, and quizzes, as well as supporting teaching staff in providing clear feedback in accordance with the activities carried out by students. The results of this study indicate that the Learning Management System using the Kanban method has met the expectations of teachers and students in the learning process.